Influence of crystallization temperature on physical and chemical properties of BiFeO3 thin films - Teixeira, Marco Antonio de Mello [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The objective of this study is to establish synthesis protocols for bismuth ferrite thin films, with a particular focus on crystallization temperature, and to evaluate the influence of these protocols on the final properties of the films. A direct correlation was identified between the selected crystallization temperatures and the formation of various types and concentrations of defects, which, in turn, modulate these properties. Our findings indicate that, within the studied temperature range, 600 °C is the ideal crystallization temperature for obtaining films with minimized defects and enhanced functional properties. The sample crystallized at this temperature exhibited a significant reduction in point -free and complex - and secondary phase defects, leading to superior performance compared to the other samples. Specifically, this sample demonstrated the lowest electrical conductivity and leakage current values, the highest percentage increase in electrical conductivity and current under green light illumination, and the highest electrical polarization values.

O objetivo deste estudo é estabelecer protocolos de síntese para filmes finos de ferrita de bismuto, com foco particular na temperatura de cristalização, e avaliar a influência destes protocolos nas propriedades finais dos filmes. Foi identificada uma correlação direta entre as temperaturas de cristalização selecionadas e a formação de vários tipos e concentrações de defeitos, que, por sua vez, modulam essas propriedades. Nossos resultados indicam que, dentro da faixa de temperatura estudada, 600 °C ´e a temperatura de cristalização ideal para obter filmes com defeitos minimizados e propriedades funcionais aprimoradas. A amostra cristalizada nessa temperatura exibiu uma redução significativa nos defeitos pontuais - livres e complexos - e fases secundarias, levando a um desempenho superior em comparação com as outras amostras. Especificamente, esta amostra demonstrou os menores valores de condutividade elétrica e corrente de fuga, o maior aumento percentual na condutividade elétrica e corrente sob iluminação de luz verde, e os maiores valores de polarização elétrica.
Influência da temperatura de cristalização sobre as propriedades físicas e químicas de filmes finos de BiFeO3
Keywords: Bismuth ferrite; Crystallization temperature; Defects; Thin films; Ferrita de bismuto; Temperatura de Cristalização; Defeitos; Filmes finos